Mobile-Based Design of Cost Estimation Calculation Application with Using Framework Cordova Case Study of Dki Jakarta Region - Malabay; Augustinus, Andreas; Tjahjono, Budi; Murnawan (International Journal of Psychosocial Rehabilitation, 2020)
Cost estimation is a part that will be used as a basis for determining whether a construction project is feasible or not, the estimated cost is also required at the beginning before the start of a project. Cost estimation has an important role for the parties involved in it such as the Project owner, Consultant Planner and contractor. In general, construction cost estimates are divided into conceptual cost estimates and detailed cost estimates. Conceptual cost estimation is the estimated cost based on the concept or general description of the building to be built, for example a modest house, a luxury home, and. Through this estimation, conceptual costs are obtained, namely costs based on a general description that becomes a reference to the planned building construction before the detailed costs are calculated. Detailed cost estimation is the estimated cost based on a detailed calculation of the quantity and unit cost of each building component so that a more accurate total cost is obtained. The data used in this study came from the Indonesian Association of Appraisers (MAPPI) and the Ministry of Public Works and Homework which have been reviewed and used in the professional world.